Customer Experience Management in the Tourism Sector: Insights from a Bibliometric and Thematic Analysis - Mourad Aarabe; Nouhaila Ben Khizzou; Lhoussaine Alla; Ahmed Benjelloun (Tourism and Hospitality, 2025)
The growing importance of customer experience management (CEM) in the tourism sector has led to a proliferation of research interests in satisfaction enhancement, loyalty, and value co-creation. This study proposes a systematic and exhaustive thematic and bibliometric analysis of 3874 articles on CEM in the tourism industry published in the Scopus database between 1979 and 2024. Following the guidelines of the PRISMA protocol, the study uses Bibliometrix (version 4.4.1) in R and VOSviewer (version 1.6.20) to map publication trends, author networks, thematic and chronological evolution, and influential contributions. A qualitative content analysis of the most cited works, guided by grounded theory, revealed the main antecedents, consequences, mediators, and moderators of customer experience management. This analysis is embodied in the proposal of a conceptual model that illustrates the dynamic relationship between these elements and provides the basis for future research for theoretical enrichment and empirical validation. The results offer actionable insights for academics and industry practitioners alike, with the aim of promoting authentic and memorable tourism experiences.